Respuesta :
Answer= 13 years
Solution,
Let the age of grandmother be y
Let the age of grandson be X
according to question,
9x=y ( equation I)
X+56=y( equation ii)
Substituting,
9x=x+56
or,9x-x=56
or,8x=56
or,X=56/8
X=7
Again,
Age of grandson after 6 years
=7 years+6 years
=13 years
Hope it helps
Good luck on your assignment
The age of her grandson after 6 years is 13 years.
What is the algebraic equation?
A mathematical statement in which two expressions are set equal to each other is known as an algebraic equation. A variable, coefficients, and constants are commonly included in an algebraic equation.
How to solve this problem?
Let the age of the grandmother be x and the age of her grandson be y.
Since the grandmother is 9 times older than her grandson, we can write
x = 9y ...(1)
Since the grandmother is 56 years older than her grandson, we can also write
x = y + 56 ...(2)
We have to solve these two algebraic equations.
Equating the L.H.S. of (1) and (2),
9y = y + 56
i.e. 9y - y = 56
i.e. 8y = 56
i.e. y = 56/8 = 7
So, now the age of her grandson is 7 years.
Therefore the age of her grandson after 6 years is 6+7= 13 years.
Know more about algebraic equations here -
https://brainly.com/question/140336
#SPJ2